Money and banking : financial markets and institutions - Smith, Gary. (Reading, Mass. : Addison-Wesley Pub. Co., 1982)
The author took a broad view of money and banks- to look across a spectrum of financial assets and institutions, trying to emphasize general principles rather than soon outdated facts. A nice vehicle the author used for doing that is a flow-of-funds framework. This displays the various types of assets that are bought and sold by specific financial institutions. The order of the chapters in the book make sense in that they are seemingly related topics. The book is divided into three parts. Part I, Financial Markets. Part II, Agents. Part III, Macroeconomic Analysis.
Includes bibliographical references and index.
rpm 27/04/2018
Loans
Keywords: Financial institutions; Money; Banks and banking